Więcej niż „trudny problem świadomości”: o możliwości powstania świadomej sztucznej inteligencji - Przybysz, Piotr (Człowiek i Społeczeństwo, 2025)
The aim of this paper is to review the most important questions and problems concerning the emergence of conscious ai. In the paper, I point out three such key questions and problems: (1) how to recognize that ai has acquired consciousness? (2) how can conscious ai emerge? and (3) what properties can conscious ai have? I argue that these problems cannot currently be solved on the basis of purely experimental, computer science, and engineering approaches, because the path to this leads through areas marked out by previous philosophical and general theoretical reflection on the subject.